Bacterial Larvicide, Bacillus thuringiensis israelensis Strain AM 65-52 Water Dispersible Granule Formulation Impacts Both Dengue Vector, Aedes aegypti (L.) Population Density and Disease Transmission in Cambodia. - To Setha; Ngan Chantha; Seleena Benjamin; Doung Socheat (Public Library of Science (PLoS), 2016)
A multi-phased study was conducted in Cambodia from 2005-2011 to measure the impact of larviciding with the bacterial larvicide, Bacillus thuringiensis israelensis (Bti), a water dispersible granule (WG) formulation on the vector, Aedes aegypti (L.) and the epidemiology. In our studies, all in-use containers were treated at 8 g/1000 L, including smaller containers and animal feeders which were found to contribute 23% of Ae aegypti pupae. The treated waters were subjected to routine water exchange activities. Pupal production was suppressed by an average 91% for 8 weeks. Pupal numbers continued to remain significantly lower than the untreated commune (UTC) for 13 weeks post treatment in the peak dengue vector season (p<0.05). Suppression of pupal production was supported by very low adult numbers in the treated commune. An average 70% of the household harbored 0-5 Ae aegypti mosquitoes per home for 8 weeks post treatment, but in the same period of time >50% of the household in the UTC harbored ≥11 mosquitoes per home. The adult population continued to remain at significantly much lower numbers in the Bti treated commune than in the UTC for 10-12 weeks post treatment (p<0.05). In 2011, a pilot operational program was evaluated in Kandal Province, a temephos resistant site. It was concluded that 2 cycles of Bti treatment in the 6 months monsoon season with complete coverage of the target districts achieved an overall dengue case reduction of 48% in the 6 treated districts compared to the previous year, 2010. Five untreated districts in the same province had an overwhelming increase of 352% of dengue cases during the same period of time. The larvicide efficacy, treatment of all in-use containers at the start of the monsoon season, together with treatment coverage of entire districts interrupted disease transmission in the temephos resistant province.